(untitled) (Journal of Asian Development Studies, 2025)
This study analyses and investigates the gender markers of the Brahui language. This research is more significant because it will give a clear understanding of the Brahui language in the region, and it will promote this language globally. This study aims to raise awareness among other language speakers, making it easier for them to attract others to this language. This study is going to explore the gender markers of nouns in the Brahui language. We will explore the understanding of gender markers in our language. I am using this theory for my research, specifically the linguistic relativity theory, established by Sapir-Whorf in 1920. The objective of this qualitative study was to explore, classify, and contribute to a broader understanding of gender markers in the Brahui language. The sampling technique used in this research was corpus analysis, such as grammar books, dictionaries, and journals. The data analysis method used was an exploratory and descriptive analysis. This study reveals that the gender markers are used in the Brahui language in different ways. Most of the gender markers in the Brahui language are formed by using prefixes and suffixes to the root word, making the noun masculine, feminine, or neutral. The suffix (Reh) marks both feminine (e.g., Irr, Masir) and masculine (e.g., mar) genders, while neutral gender lacks such markers, using separate terms (Naringa, Madainga) instead. This will enhance the awareness of gender markers among other speakers.